Etika dan Kode Etik Hukum Arsitek Dalam Industri Konstruksi di Indonesia - Simanjuntak, Manlian Ronald Adventus (LAW REVIEW, 2002)
Ethics and code of ethics have actually different meanings in construction industry, especially an Architect as a designer in planning process. These words will be discussed and analyzed in this paper which is important for an A rchitect in doing their professional responsibility making the design. There are few aspects that will be discuss in this paper correlating to the ethics and the code ethics of Architect that will be compare to the Law System in Indonesia. By awareness to all the aspects of ethics and code of ethics of professional architect, the construction industry process will be implemented well for the future in Indonesia.Â